An Integrated Approach for Risk Management of Hazmat Transportation: Use of Quality Function Deployment and Risk Assessment - Zhigerbayeva, Guldana (Nazarbayev University School of Engineering and Digital Sciences, 2020)
Various methods have been developed to ensure the safe transportation of hazardous materials (HAZMAT) transportation. These methods mainly include tree-based methods with fault-trees, event-trees and cause-consequence analysis, Bayesian network, and statistical methods. However, these methods cannot provide a systematic approach to risk management of HAZMAT transportation. They do not intend to build up the linkages between the regulatory requirements and the safety measures development. The analysis of historical data from the past accidents' report databases would limit our focus on the specific incidents and their causes. Thus, we may overlook some essential elements in risk management, including regulatory compliance, field expert opinions, and suggestions. It is necessary to develop a systematic approach that can translate the regulatory requirements of HAZMAT transportation into specified safety measures (both technical and administrative) to support the risk management process. This study aims to develop a novel decision supporting system (DSS) that integrates the Quality Function Deployment (QFD) and risk assessment, namely Safety Function Deployment (SFD), to identify potential risks and find an optimal route for HAZMATs transportation. The proposed framework utilizes the risk-based and routes analysis SFD to create House of Safety (HoS) as a core element. Besides, the cost of transportation will also be considered. The SFD estimates the safety of a final path, considering harsh environmental and other risk factors.
Keywords: Quality Function Deployment; Safety Function Deployment; Department of Transportation; Hazardous Material; Hazard and Operability analysis; Layer of Protection Analysis; Risk Assessment; Preliminary Hazard Analysis; Fault tree analysis; FTA; QFD; SFD; Analytical hierarchy process; Research Subject Categories::TECHNOLOGY